1979
DOI: 10.1073/pnas.76.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Binding site on macrophages that mediates uptake and degradation of acetylated low density lipoprotein, producing massive cholesterol deposition

Abstract: ABSTRACIResident mouse peritoneal macro hages were shown to take up and degrade acetylated 1251 abeled low density lipoprotein (15I-acetyl-LDL) in vitro at rates that were 20fold greater than those for the uptake and degradation of 125I-LDL. The uptake of 1251-acetyl-LDL and its subsequent degradation in lysosomes were attributable to a high-affinity, trypsin-sensitive, surface binding site that recognized acetyl-LDL but not native LDL. When 25I-acetyl-LDL was bound to this site at 4VC and the macrophages were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
973
0
34

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,098 publications
(1,028 citation statements)
references
References 22 publications
12
973
0
34
Order By: Relevance
“…When the MDMs obtained with the 11 protocol described above were cultured for 1 h in the presence of Alexa 488-conjugated AcLDL, they internalized AcLDL and transformed into foam cells. SR-A is a major macrophage receptor responsible for the uptake of modified LDL (Goldstein et al, 1979;Kunjathoor et al, 2002). We confirmed that SR-A expression was frequently detected in AcLDL-loaded MDMs generated by our new method (Figure 2D We showed that MDMs can be induced by coculture with autologous non-adherent PBMCs without adding any growth factors (Figure 2).…”
Section: Mdms Loaded With Acldl Express Mica/bsupporting
confidence: 72%
See 1 more Smart Citation
“…When the MDMs obtained with the 11 protocol described above were cultured for 1 h in the presence of Alexa 488-conjugated AcLDL, they internalized AcLDL and transformed into foam cells. SR-A is a major macrophage receptor responsible for the uptake of modified LDL (Goldstein et al, 1979;Kunjathoor et al, 2002). We confirmed that SR-A expression was frequently detected in AcLDL-loaded MDMs generated by our new method (Figure 2D We showed that MDMs can be induced by coculture with autologous non-adherent PBMCs without adding any growth factors (Figure 2).…”
Section: Mdms Loaded With Acldl Express Mica/bsupporting
confidence: 72%
“…Infiltrating macrophages accumulate in fatty streak lesions and transform into foam cells, which then undergo necrotic or apoptotic cell death in loco, leading to the formation of atherosclerotic plaques (Sakakura et al, 2013). The class A scavenger receptor (SR-A) is a major macrophage receptor responsible for the uptake of modified low-density lipoprotein (LDL) such as oxidized LDL and acetylated LDL (AcLDL) (Goldstein et al, 1979;Kunjathoor et al, 2002) that converts macrophages into foam cells. Thus, SR-A expression is frequently observed in atherosclerotic lesions (Naito et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages were shown to take up acetylated LDL by specific receptor-mediated processes (Goldstein et al, 1979). BDE cultures were exposed to 1,1'-dioctadecyl-3,3,3',3'-tetramethylindo-carbocyanine perchlorate-acetylated lowdensity lipoprotein (DiI-Ac-LDL) at 10 gg per ml of 10% DMEM for 4 h at 370 C according to the manufacturer's instructions (Biomedical Technologies Inc., Stoughton, MA).…”
Section: Methodsmentioning
confidence: 99%
“…In order to test the two alternatives-sprouting or angioblastic recruitment-we used specific markers for the angiogenic cell lineage. By in vivo application of acetylated low density lipoprotein coupled to the fluorescent probe 1,l 'dioctadecyl-l-3,3,3',3'-tetra-methyIindo-carbocyanine perchlorate (DiI-Ac-LDL), it is possible to label endothelial cells and macrophages (Goldstein et al, 1979;Stein and Stein, 1980;Voyta et al, 1984), while the QH-1 antibody (Pardanaud et al, 1987) is specific for haemangioblasts of the quail. Using a double-labelling procedure, we expected to discriminate between isolated angioblasts originating from patent vessels by sprouting and angioblasts recruited from limb bud mesoderm.…”
Section: Introductionmentioning
confidence: 99%